2009
DOI: 10.1007/s10792-009-9328-5
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal granuloma as an initial manifestation of systemic sarcoidosis

Abstract: Systemic sarcoidosis presenting as a choroidal nodule is a rare phenomenon, with limited reports in the past. We present a case of systemic sarcoidosis in a young adult male presenting as a solitary choroidal mass. The diagnosis was made based on elevated serum lysozyme, serum angiotensin-converting enzyme, negative Mantoux, and computed tomography (CT) scan of the chest. Ultrasound examination and fundus fluorescein angiography helped us to differentiate this lesion from choroidal melanoma. Magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Choroidal granulomas manifesting as the sole lesion in ocular sarcoidosis has been previously described [1,7-10]. Desai et al reported on the largest case series of choroidal granulomas in nine patients with biopsy-proven sarcoidosis [1].…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal granulomas manifesting as the sole lesion in ocular sarcoidosis has been previously described [1,7-10]. Desai et al reported on the largest case series of choroidal granulomas in nine patients with biopsy-proven sarcoidosis [1].…”
Section: Discussionmentioning
confidence: 99%
“…On EDI-OCT, Choroidal granulomas appeared as hyporeflective thickening of the choroid [2628]. On FA, the lesions can demonstrate hypofluorescence, isofluorescence, early blocking with late staining, and hyperfluorescence [26, 29, 30]. Many reports have described the choroidal granulomas as hypofluorescent on ICGA [28, 31].…”
Section: Main Textmentioning
confidence: 99%
“…This was around 95% in those who presented to the tertiary eye care center probably due to the referral bias [9]. Ocular manifestations include uveitis, dry eye, conjunctival granulomas, and involvement of the orbit and optic nerve [9,10,18-21,34]. …”
Section: Reviewmentioning
confidence: 99%